Using virtual reality to support autistic employees: a perspective on creating inclusive neurodiverse work environments - Tatom, Roderick C.; Newbutt, Nigel (Frontiers in Virtual Reality, 2025)
The double empathy problem underscores a two-way gap in understanding between autistic and neurotypical individuals, contributing to systemic barriers in workplace communication and inclusion. Virtual reality (VR) technologies offer immersive, low-pressure environments for autistic users to build confidence, regulate stress, and navigate high-stakes workplace interactions. A strengths-based approach to VR design emphasizes autistic individuals’ unique capabilities, such as attention to detail and innovative problem-solving, by incorporating user feedback, customizable prompts, and participatory co-design. To advance equity in neurodiverse employment, this paper concludes with five actionable strategies that position VR as a vehicle for systemic change, empowering autistic professionals and encouraging organizations to adopt inclusive design, universal learning principles, and long-term evaluation metrics.